ENVIRONMENTAL IMPLICATIONS OF POPULATION GROWTH, FOREIGN DIRECT INVESTMENT AND TRADE OPENNESS IN SAARC AND ASEAN COUNTRIES: AN EXTENDED STRIPAT APPROACH - Mubashir Ishfaq; Muhammad Jawad Asghar Shah; Muhammad Muzammil Asghar; Muhammad Adeel Abbas; Muhammad Arshad (International Journal of Contemporary Issues in Social Sciences, 2024)
This study analyzes the environmental implications of population growth, FDI and trade openness in SAARC and ASEAN countries using the panel dataset from 1971 to 2019. Panel unit root tests, Pedroni test of cointegration, panel ARDL method and Granger causality tests are used to estimate the results. The outcomes reveal that population growth rate, GDP per capita, GCF, FDI and industrialization are positively and significantly related to environmental degradation. On the other hand, the relationship between trade openness and environmental degradation is positive but statistically insignificant. It is concluded that population growth and FDI inflows are creating environmental problems in SAARC and ASEAN countries. Therefore, it is suggested that policymakers should design policies to control the population, encourage environmentally friendly capital inflows, and encourage the use of green energy resources to reduce environmental degradation.